2017
DOI: 10.1016/j.envint.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate and fine particulate matter on hospitalizations and deaths for heart failure in elderly: A population-based cohort study

Abstract: Lag effects of temperature and other meteorological parameters on HF events were limited but present. Nonetheless, preventive measures should be issued for elderly diagnosed with HF considering the burden and the expensive costs associated with the management of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
(55 reference statements)
2
25
1
Order By: Relevance
“…Furthermore, an accumulation of PM10 during 10 days prior to death significantly increased the mortality incidents due to cerebrovascular disease and chronic lung disease. Also, while a study from Japan published in 2013 found that a maximum 8 hours of 10 ppb increase in ozone was associated with 0.69% increase in mortality incidence,62 studies conducted in Canada and Finland did not find any lag effects in terms of the effect of air pollutant on the association between heart failure and cardiopulmonary disease with mortality 6364. Accordingly, each air pollutant influenced mortality incidents differently in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, an accumulation of PM10 during 10 days prior to death significantly increased the mortality incidents due to cerebrovascular disease and chronic lung disease. Also, while a study from Japan published in 2013 found that a maximum 8 hours of 10 ppb increase in ozone was associated with 0.69% increase in mortality incidence,62 studies conducted in Canada and Finland did not find any lag effects in terms of the effect of air pollutant on the association between heart failure and cardiopulmonary disease with mortality 6364. Accordingly, each air pollutant influenced mortality incidents differently in our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Congestive heart failure (CHF) is a serious public concern because of its poor prognosis [ 1 ] and considerable economic impact on health services, given that it affected 40.0 million people worldwide in 2015 [ 2 ]. Epidemiological studies from developed countries have extensively reported that acute exposure to fine particulate matter (PM 2.5 ) has a close temporal association with hospitalization for and mortality from CHF [ 3 , 4 , 5 ], especially in patients with histories of diabetes [ 6 ] and hypertension [ 7 ]. A meta-analysis published in 2013 reported that increasing PM 2.5 daily concentrations by a unit of 10 μg/m 3 would contribute to an estimated 2.12% increase in hospitalization for CHF and CHF mortality globally [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of this study might be valid for other veterinary centers located in geographic areas with a similar climate but cannot be generalized to all veterinary centers. Third, other climatic factors, including relative humidity, atmospheric pressure, and air pollutant exposure [40], or patient-related factors, including percentage of time the dog spent indoor/outdoor and access to indoor climate control (i.e., heating and airconditioning), not measured in this study can have an effect on development and outcome of CHF. Finally, the ambient temperature data were obtained from the VTH location from the website.…”
Section: Discussionmentioning
confidence: 99%